Through-bond orbital coupling in end-functionalized bicyclohexylidenes: photoelectron spectroscopy and ab initio SCF-MO calculations - Marsman, Albert W.; Havenith, Remco W. A.; Bethke, Sabine; Jenneskens, Leonardus W.; Gleiter, Rolf; Lenthe, Joop H. van (European journal of organic chemistry, 2000)
To establish whether through-bond (TB) orbital interactions occur between the functional groups and the hydrocarbon skeleton in a series of end-functionalized oligo(cyclohexylidenes) 1−12, their HeI photoelectron (PE) spectra were measured and analyzed. Vertical ionization energies, Ivj, of the highest occupied molecular orbitals (MOs) of 1−12 were assigned using ab initio RHF/6−31G* MO energies (−ϵj) in combination with Koopmans’ theorem. Excellent to good agreement was found between the PES and RHF/6−31G* results. In addition, the Ivj, assignments were further corroborated by a comparison of the PES data of 1−12 with those previously reported for appropriate reference compounds 13−20. To assess contributions from through-bond (TB) and/or through-space (TS) interactions, RHF/6−31G*/NBO analyses were performed. The results show that in the cases of 1−12, TS interactions do not occur. TB interactions were unequivocally identified for 1−4, 8, 10 and 11−12. These TB interactions were found to be relayed via the Hax−C−C−Hax precanonical σ-MOs (σ-PCMOs) of the cyclohexyl-like moieties.
Gesehen am 27.10.2020